1983
DOI: 10.1620/tjem.141.suppl_161
|View full text |Cite
|
Sign up to set email alerts
|

The significance of certain epidemiological variants in the genesis of juvenile insulin-dependent diabetes mellitus - The need for a global program of co-operation.

Abstract: Published data from literature show a two-to four-fold increase in the incidence of JIDDM, in the Western hemisphere over the past decade (5% to 10-20%). WHO Expert Committee Technical Report Series No. 646 (1980) gives the risk of development of diabetes in the first two decades of life, in the sub-populations of Europe and North America, as 0.1% to 0.3%. In Japan, it is stated to be less than 0.02% ; in Tamil Nadu, India, we have calculated the risk to be less than 0.01%. The incidence of JIDDM amongst diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Lack of access to, and the high cost of, insulin and other supplies, limited health professional expertise concerning childhood diabetes, lack of diabetes education, geographic isolation and extreme poverty can result in very poor outcomes-starting with frequent misdiagnosis at disease onset so the child dies untreated; then a high risk of early death from hypoglycaemia or ketoacidosis; and for those who survive, very poor blood glucose control. Such sustained poor control leads to impaired quality of life and develop severe complications (such as loss of vision, end-stage renal failure and severe neuropathy) in their 20s or even earlier [8]. But with the advent of this new modality of treatment (DAMM Therapy) the cost of treatment will be greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of access to, and the high cost of, insulin and other supplies, limited health professional expertise concerning childhood diabetes, lack of diabetes education, geographic isolation and extreme poverty can result in very poor outcomes-starting with frequent misdiagnosis at disease onset so the child dies untreated; then a high risk of early death from hypoglycaemia or ketoacidosis; and for those who survive, very poor blood glucose control. Such sustained poor control leads to impaired quality of life and develop severe complications (such as loss of vision, end-stage renal failure and severe neuropathy) in their 20s or even earlier [8]. But with the advent of this new modality of treatment (DAMM Therapy) the cost of treatment will be greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics gathered from the survey the risk of JIDDM to be <0.01%. And the authors have suggested that this figure may rise to as much as 0.02% or 0.04%, depending upon the regional variations in a vast multifaceted country like India [8].…”
Section: Introductionmentioning
confidence: 99%